An efficient 3D stack‐of‐stars turbo spin echo pulse sequence for simultaneous T2‐weighted imaging and T2 mapping. Issue 1 (18th March 2019) - Keerthivasan, Mahesh Bharath; Saranathan, Manojkumar; Johnson, Kevin; Fu, Zhiyang; Weinkauf, Craig C.; Martin, Diego R.; Bilgin, Ali; Altbach, Maria I.
Abstract : Purpose: To design a pulse sequence for efficient 3D T2‐weighted imaging and T2 mapping. Methods: A stack‐of‐stars turbo spin echo pulse sequence with variable refocusing flip angles and a flexible pseudorandom view ordering is proposed for simultaneous T2‐weighted imaging and T2 mapping. An analytical framework is introduced for the selection of refocusing flip angles to maximize relative tissue contrast while minimizing T2 estimation errors and maintaining low specific absorption rate. Images at different echo times are generated using a subspace constrained iterative reconstruction algorithm. T2 maps are obtained by modeling the signal evolution using the extended phase graph model. The technique is evaluated using phantoms and demonstrated in vivo for brain, knee, and carotid imaging. Results: Numerical simulations demonstrate an improved point spread function with the proposed pseudorandom view ordering compared to golden angle view ordering. Phantom experiments show that T2 values estimated from the stack‐of‐stars turbo spin echo pulse sequence with variable refocusing flip angles have good concordance with spin echo reference values. In vivo results show the proposed pulse sequence can generate qualitatively comparable T2‐weighted images as conventional Cartesian 3D SPACE in addition to simultaneously generating 3D T2 maps. Conclusion: The proposed stack‐of‐stars turbo spin echo pulse sequence with pseudorandom view ordering and variable refocusing flip angles allows high resolution isotropic T2 mapping in clinically acceptable scan times. The optimization framework for the selection of refocusing flip angles improves T2 estimation accuracy while generating T2‐weighted contrast comparable to conventional Cartesian imaging.